Assymptotic solutions in the ultrasonic corrosion control - Popov, Alexander; Michovski, Mitko (Ann. Sofia Univ. Fac. Math. and Inf., 1996)
Ultrasonic method for intercrystalline corrosion in austerinic steels is presented. The ultrasonic waves propagation is described by eikonal equation. The information parameters for intercrystalline corrosion testing are the time of propagation and the distance between ultrasonic transducers (transmiter and receiver). Testing criteria are proposed.